Defects in Epitaxial lift-off Thin Si Films/Wafers and Their Influence on the Solar Cell Performance. Issue 1666 (3rd November 2014) - Sopori, Bhushan; Devayajanam, Srinivas; Basnyat, Prakash; Moutinho, Helio; Reedy, Robert; VanSant, Kaitlyn; Ravi, T.S.; Hao, Ruiying; Vatus, Jean; Nag, Somnath
ABSTRACT: In this paper, we will describe the nature of defects and impurities in thick epitaxial-Si layers and their influence on the cell efficiency. These wafers have very low average dislocation density. Stacking faults (SFs) are the main defect in epi layers. They can occur in many configurations—be isolated, intersecting, and nested. When nested, they can be accompanied by formation of coherent twins resulting in dendritic growth, with pyramids protruding out of the wafer surface. Such pyramids create large local stresses and punch out dislocations. The main mechanism of dislocation formation is through pyramids. Stacking faults degrade solar cell performance. Analyses of the solar cells have revealed that the nested SFs have a controlling effect on the solar cell performance. A well-controlled growth can minimize defect generation and produce wafers that can yield cell efficiencies close to 20%.